Informal Social Networks and Mate Selection: Retrospective Experiences of Divorced Individuals - , Kiran Ikram; Tayyaba Sohail; Ahmed Usman; Nadeem, Mudasar (Italian Sociological Review, 2026)
The present study explores the retrospective experiences of divorced individuals in the mate selection process in Pakistan. In the socio-cultural, traditional, and collectivistic context of Pakistani society, considering the importance of the mate selection process in marriage and divorce, as well as the role of informal social networks in mate selection, is an emerging yet overlooked phenomenon. Informal social networks, particularly among close and extended family members, provide support in times of need as a benefit of adhering to the network’s obligations. They can also withdraw this support from any individual if they deviate from the social norms regulating the network. Thus, family and informal networks provide and control choices, opinions, resources, and decisions regarding marriage. Hence, an individual is highly dependent on them when making life decisions and the structure provides or withdraws support accordingly. The study examines the role of informal social networks in the mate selection process and their gender dynamics, focusing on divorced individuals to explore the navigation between personal desires and collective obligations within the context of power and gender dynamics. The methodological stance is purely qualitative, involving 14 in-depth interviews until saturation is reached. The data has been analysed thematically. The study sample was recruited through purposive sampling. The study’s findings illustrate the manifestation of gender and power dynamics in the process of mate selection through informal social networks, indicating different privileges and opportunities for both genders. The narratives of the respondents also reflected that the intervention of the extended family sometimes leads to mismatches, based on materialistic needs, and these factors play an essential role in relation breakups and divorce. The study highlights the need to re-evaluate the framework of decision-making in marriages as a step towards stable marriages.